Luke's unique parables: Genesis narratives and interpretations of Jesus - Carmichael, Calum M. (Cambridge University Press, 2025)
"Calum Carmichael presents a new perspective on how parables unique to Luke's Gospel were composed. Providing literary and linguistic analyses, he demonstrates how Luke, like many of his contemporaries, absorbed the narrative legacy of the Hebrew Bible and used it to express ideas about Jesus"--